AIDA – Experiences in Compensating the Mutual Weaknesses of Knowledge-based and Object-oriented Development in a Complex Dental Planning Domain - Finkeissen, E.; Weber, R.; Haßfeld, S.; Koke, U.; Wetter, T. (Methods of Information in Medicine, 2002)
Objectives: Dentistry is a discipline with two properties that pose a serious challenge to knowledge based decision support: (1) It has to integrate six sub-disciplines ranging from conservative measures to invasive disciplines, such as implantology; (2) A plan may have to cover a complex treatment often lasting one year or more. It is the aim of the AIDA-project1 to set up a planning strategy that is suited to incorporate all dental peculiarities in one methodology.Methods: Generic tasks, that can be assigned to individual persons involved in dental treatment, have been designed with the help of KADS. They have been integrated into a planning super-structure for the planning of all dental solution alternatives, that can principally be applied on the basis of the given patient status.Results: Besides an evaluation of the implemented planning system itself, it has been evaluated how well the development is supported by (1) knowledge-engineering methods and (2) object-oriented methods.Conclusion: Common knowledge-based tools are not powerful enough for the planning of complex dental constructions. Therefore, a solution combining object-oriented and knowledge-based methods is proposed.
Keywords: Dentistry; decision making; theoretical models; knowledge; decision support techniques